Exploring the Significance of Arabic Language Proficiency in Contemporary Education: Insights from Indonesian Students in Tunisia - Abdunrorma Samaalee; Ead Hamed; Ahmadi (IJCRE - International Journal of Culture, Religion, and Education, 2025)
Arabic language proficiency is increasingly crucial in the field of education, particularly for studying the Al-Qur’an and hadith, which are predominantly in Arabic. Thus, acquiring Arabic skills is essential for enhancing foreign language communication, especially in everyday contexts. This study focuses on Indonesian students pursuing further education in Tunisia, employing qualitative research methodology to investigate the impact of learning Arabic on cultural awareness and appreciation among these students. The research emphasizes the significance of recent findings in guiding further inquiry. By examining various techniques and educational approaches, the study highlights the transformative potential of the Arabic language learning process in Tunisian schools. This integration of Arabic language instruction with other subjects fosters an effective learning environment, particularly for Indonesian students, facilitating proficiency in muhadatsah, kitabah, qiro’ah, and Istima’. Ultimately, implementing the appropriate educational strategies cultivates competent Arabic language learners and promotes a culture of Arabic language acquisition among Indonesian students.